Effects of breakwater location on breakwater performance / Yuslina Mohd Sani - Mohd Sani, Yuslina (1998)
A study was conducted in the laboratory to determine the effects of breakwater location on its ability to absorb the wave action. A model breakwater was constructed in the wave basin using aggregates measurements were carried out to measure the wave heights in front and behind the breakwater. Tests were conducted for two difference breakwater locations under different wave conditions. Results were presented to show the breakwater absorption in terms of reduction in the wave heights measured in front and behind the breakwater.